China and Western Aid Norms in the Belt and Road: Normative Clash or Convergence? A Case Study on Ethiopia. Issue 134 (4th March 2022) - Esteban, Mario; Olivié, Iliana
ABSTRACT: Despite considerable debate on the normative foundations of Chinese international development cooperation and how they compare with those of traditional donors, positivist studies on the normative consequences of China's socialization into mainstream international norms of development assistance are scarce. This article explores this topic for the case of Ethiopia, an aid 'darling' with an extended presence of Chinese and Western development actors, taking the Aid Effectiveness Agenda as reference. Resorting to official documents, data analysis, and semi-structured interviews, the authors find that Chinese development actors' understanding of ownership and transparency is relatively stable and different from that of Western donors and that they promote their own understanding of those principles among Ethiopian stakeholders. There are, however, significant changes in inclusive partnerships and the focus on results, that have more to do with a pragmatic adaptation process by Chinese actors than with a socialization process through their interaction with traditional donors.